Moral Stories Can Promote Honesty in Chinese Young Children - Yanyan Sai; Mo Zheng; Yeqing Tang; Liyang Sai; Xue Liu (Behavioral Sciences)
Stories are widely used by parents or educators to teach children the virtue of honesty. However, the existing empirical findings on the effect of story-telling on children’s honesty are limited and mixed. This study examined whether moral stories involving honesty can promote honesty in Chinese preschool children (N = 208). The Temptation Resistance Paradigm (TRP) was used to assess children’s honesty. Study 1 showed that children in the positive moral story condition were more likely to tell the truth than those in the control condition, while negative moral story-telling did not have this effect. Study 2 further examined whether combining external appeals with positive moral story-telling could further promote children’s honesty, and the results showed that the combination of the two techniques was equally as effective as moral story-telling alone. These findings have important implications for moral development and moral education.